Anthropology and public health bridging differences in culture and society - Hahn, Robert A., 1945-; Inhorn, Marcia Claire, 1957- (New York ; Oxford : Oxford University Press, 2009)
Through 24 case studies from around the world, the volume provides a powerful argument for the imperative of anthropological perspectives, methods, information, and collaboration in the understanding and practice of public health.
Previous ed.: published as Anthropology in public health. 1999.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Public health -- Anthropological aspects -- Developing countries